Sensory shelf life of mantecoso cheese using accelerated testing - Sánchez-González, Jesús A. (2016)
The aim of this research was to estimate sensory shelf life of "huacariz" and "cefop" mantecoso cheese, vacuum packaging: "cefop" and packaging to the atmospheric pressure: "huacariz"; brands marketed in Cajamarca, using accelerated shelf life testing. For this purpose, "huacariz" cheese was stored at 20, 28, 35 y 40 °C, while it was set at 20, 28, 35 °C storage for "cefop" cheese, performing acceptability sensory tests according to time storage with both 41 consumers constants. The results from sensory analysis were analyzed by software R for survival analysis statistics applied to sensory shelf life of foods. For this, Weibull distribution was applied and allowed to know shape (β) and scale (α) parameters, just being β value necessary to know the reliability of the raw data. The accelerated storage at temperatures close to 35 ºC yielded values of β < 2, for both cheeses, by the sensory way these samples had variability of consumer acceptability and swift rejection by altering the structure of the cheese which started to flow. Activation energy (Ea) was evaluated for both mantecoso cheeses: atmosphere packaging ("huacariz") and vacuum packaging ("cefop"), getting an Ea value 14.26 ± 3.25 kcal/mol and 22.61 ± 5.92 kcal/mol corresponding to "huacariz" and "cefop" mantecoso cheese, respectively. Sensory shelf life of "huacariz" and "cefop" mantecoso cheese at 10 °C storage was about 7.6 and 41.7 days, respectively.